Effect of the content of B4C on microstructural evolution and wear behaviors of the laser-clad coatings fabricated on Ti6Al4V. (January 2016) - Bai, L.L.; Li, J.; Chen, J.L.; Song, R.; Shao, J.Z.; Qu, C.C.
Abstract: TiNi/Ti2 Ni-based composite coatings reinforced by TiC and TiB2 were produced on Ti6Al4V by laser cladding the mixture of a Ni-based alloy and different contents of B4 C (0 wt%, 5 wt%, 15 wt%, and 25 wt%). The macromorphologies and microstructures of the coatings were examined through optical microscopy, X-ray diffractometry, scanning electron microscopy, and energy dispersive spectrometry. The microhardness, fracture toughness, and wear behaviors of the coatings were also investigated by using a microhardness tester and an ultra-functional wear testing machine. Results showed that the coatings were mainly composed of TiNi/Ti2 Ni and TiC/TiB2 as the matrix and reinforcement particles, respectively. The phase constituents of the coatings were not influenced by addition of different contents of B4 C. The microstructure of the reinforcements in the coatings presented the following evolution: hypereutectic consisting of blocky (TiC+TiB2 )e eutectic and primary TiCp cellular dendrites (0 wt% B4 C), mixture of hypereutectic and willow-shaped (TiB2 +TiC)p pseudoeutectic (5 wt% B4 C), and pseudoeutectic (15 and 25 wt% B4 C). With increasing B4 C content, the volume fraction and size of the pseudoeutectic structures as well as the average microhardness of the coatings (850, 889, 969, and 1002 HV0.2 ) were increased. By contrast, the average fracture toughness of the coatings was gradually decreased (4.47, 4.21, 4.06, and 3.85 Mpa m 1/2 ) along with their wear volumes (0 wt%, 5 wt%, and 15 wt% B4 C). The increase in B4 C content to 25 wt% did not further reduce wear loss. The wear mechanism transformed from micro-cutting (0 wt% B4 C) into a combination of micro-cutting and brittle debonding (5 wt% B4 C) and finally led to brittle debonding (15 wt% and 25 wt% B4 C). Coatings with suitable contents of B4 C (less than 15 wt%) showed excellent comprehensive mechanical properties. Highlights: TiC+TiB2 reinforced TiNi/Ti2Ni matrix coatings were fabricated by laser cladding. The microstructural evolution of the reinforcements was analyzed. The changes of microhardness and fracture toughness were studied. Wear behaviors were investigated by wear tests. The transformation of wear mechanism of the coatings was revealed.